215k views
5 votes
Given: ∠A and ∠B are complementary angles. m∠A=3x+105 ; m∠B=−6x−39 Prove: m∠B=9° Drag and drop reasons into the boxes to correctly complete the proof. Statement Reason

∠A and ∠B are complementary angles. Given
m∠A=3x+105 ; m∠B=−6x−39 Given
m∠A+m∠B=90° Definition of complementary angles
3x+105−6x−39=90 Substitution Property of Equality
−3x+105−39=90 Simplify.
−3x+66=90 Simplify.
−3x=24
 x=−8
 m∠B=−6(−8)−39
 m∠B=48−39 Simplify.
m∠B=9°

User Evanr
by
7.0k points

2 Answers

7 votes

Given:
\angle A and
\angle B are complementary angles.


m \angle A = 3x+105^\circ and
m \angle B = -6x-39^\circ.

To prove:
m \angle B = 9^\circ

Proof:

Statement 1:
\angle A and
\angle B are complementary angles.

Reason 1: Given

Statement 2:
m \angle A = 3x+105^\circ and
m \angle B = -6x-39^\circ.

Reason 2: Given

Statement 3:
m \angle A + m \angle B = 90^\circ

Reason 3: Definition of complementary angles.

Statement 4:
3x+105^\circ -6x -39^\circ = 90^\circ

Reason 4: Substitution property of equality

Statement 5:
-3x+105^\circ-39^\circ = 90^\circ

Reason 5: Simplification

Statement 6:
-3x+66^\circ = 90^\circ

Reason 6: Simplification

Statement 7:
-3x = 24^\circ

Reason 7: Simplification

Statement 8:
x = -8

Reason 8: Multiplication property of equality

Statement 9:
m \angle B = -6(-8) - 39^\circ

Reason 9: Substituting the value of 'x'

Statement 10:
m \angle B = 48-39 = 9^\circ

Reason 10: Simplification


User Eyup Can ARSLAN
by
5.4k points
7 votes

Answer:

Statement: -3x=90-66

Reason: By subtraction property of equality..

Statement: -3x=24

Reason: By simplification.

Statement: x=
(24)/(-3)

Reason: By division property of equality.

Statement:
m\angle B= -6(-8)-39

Reason: By substitution property of equality.

Statement:
m\angle B=9^(\circ)

Reason: By simplification.

Explanation:

Given
\angle A and
\angle B are complementary angles.


m\angle A= 3x+105


m\angle B=-6x-39

To prove that
m\angle B=9^(\circ)

Proof:

1.Statement:
\angle A\; and\; \angle B are complementary angles .

Reason: Given .

2.Statement:
m\angle A=3x+105;
m\angle B= -6x-39

Reason: Given .

3. Statement:
m\angle A+ m\angle B=90^(\circ)

Reason: By definition of complementary angles.

4.Statement:
3x+105-6x-39=90

Reason: By substitution property of equality.

5. Statement:
-3x+105-39=90

Reason: By simplification.

6. Statement:
-3x+66=90

Reason: By simplification.

7. Statement:
-3x= 90-66

Reason: By subtraction property of equality .

8.Statement:
-3x=24

Reason: By simplification.

9.Statement:
x=(24)/(-3)

Reason : By division property of equality.

10. Statement: x=-8

Reason: By simplification.

11. Statement:
m\angle B= -6(-8)-39

Reason : By substitution property of equality.

12. Statement:
m\angle B= 48-39

Reason: By simplification.

13. Statement:
m\angle B=9^(\circ)

Reason : By simplification.

Hence,
m\angle B= 9^(\circ)

Hence proved.

User Adrian Conlon
by
5.6k points